Antigenic Components of Chemical Bivalent Cholera Vaccine, Methods of their Isolation and Control - S. A. Vorob’eva; O. S. Durakova; O. V. Gromova; O. A. Volokh; O. D. Klokova; A. K. Nikiforov (Проблемы особо опасных инфекций, 2022)
The paper presents a review of the data on the methods of isolation and control of Vibrio cholerae antigens – cholerogen-anatoxin and O-antigens of Inaba and Ogawa – components of the oral bivalent chemical cholera vaccine produced by the RusRAPI “Microbe”, the only prophylactic drug against cholera registered in the territory of the Russian Federation. Currently, the vaccine is produced using the method of segregated manufacturing of cholerogenanatoxin and O-antigens Inaba and Ogawa with step-by-step control of their main properties, which ensures the production of a high-quality finished product. Ultrafiltration is an effective method for concentrating a semi-finished product, which helps to reduce losses and increases the yield of the final product. It remains promising to develop a method for gentle steril ization of O-antigens to maximize the preservation of specific activity. To control the specific activity of the antigenic components and the finished vaccine preparation, a complex of in vivo and in vitro methods is applied. However, the multi-stage process and duration, the use of several types of laboratory animals, as well as modern WHO requirements determine the need for the introduction of alternative in vitro control methods. The use of cell cultures as a replacement for the biological method appears prospective, and demonstrates a positive correlation with animal tests. To assess the activity of antigens, the use of an immunochemical method – dot-immunoassay with gold nanoparticles – is put forward, which will make it possible to harmonize the control method at all stages of the production process, as well as to determine the serovar specificity of Vibrio cholerae O-antigens. The development of molecular-genetic, microbiological, immunochemical methods is relevant for a more complete and comprehensive control of the main immunogens of industrial strains of cholera vibrio. The introduction of promising methods for obtaining antigens and monitoring their properties will allow for a more complete characterization of the component composition of the finished dosage form of the chemical cholera vaccine.